2001
DOI: 10.1006/jmaa.2001.7668
|View full text |Cite
|
Sign up to set email alerts
|

Series Expansion and Reproducing Kernels for Hyperharmonic Functions

Abstract: First we show that any hyperbolically harmonic (hyperharmonic) function in the unit ball B in n has a series expansion in hyperharmonic functions, and then we construct the kernel that reproduces hyperharmonic functions in some L 1 B space. We show that the same kernel also reproduces harmonic functions inElsevier Science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In [7] it is shown that if f ∈ h(B N ) then there exists a unique sequence of harmonic homogeneous polynomials f k , of degree k, f k ∈ H k (R N ), such that…”
Section: Hyperharmonic Functions Having a Distribution Valuementioning
confidence: 99%
“…In [7] it is shown that if f ∈ h(B N ) then there exists a unique sequence of harmonic homogeneous polynomials f k , of degree k, f k ∈ H k (R N ), such that…”
Section: Hyperharmonic Functions Having a Distribution Valuementioning
confidence: 99%